Increasing Indonesia-Timor Leste Borders Diplomacy through Community-Based Health Security - Madu, Ludiro; Nugraha, Aryanta; Kusumo, Yudhy (Global Strategis, 2025)
This research focuses on the growing importance of health security in Indonesia-Timor Leste border diplomacy after the Covid-19 pandemic. This study uses qualitative methods to reveal a paradigm shift from traditional security to non-traditional security, especially health. The data comes from observations and documents collected in border areas related to health security in response to cross-border threats in both countries. The community-based health security perspective is used to analyze the expansion of health threats and the role of border diplomacy in addressing public health threats. This analysis reveals three important issues: (1) redefining the border security paradigm, (2) positioning border health security diplomacy as a collaborative mechanism, and (3) the participation of border communities in border security diplomacy. This research makes an important contribution to the development of a collaborative model of border health security diplomacy through community participation in improving health security in the border areas of the two countries. The findings offer an alternative health security policy in border diplomacy between Indonesia and Timor Leste and other border areas in Indonesia. Keywords: Border health security, Health diplomacy, Community empowerment, Indonesia-Timor Leste, Covid-19 Penelitian ini berfokus pada semakin pentingnya keamanan kesehatan dalam diplomasi perbatasan Indonesia-Timor Leste pasca pandemi Covid-19. Penelitian ini menggunakan metode kualitatif untuk mengungkapkan pergeseran paradigma dari keamanan tradisional ke keamanan non-tradisional, khususnya kesehatan. Data tersebut berasal dari pengamatan dan dokumen yang dikumpulkan di daerah perbatasan terkait keamanan kesehatan dalam menanggapi ancaman lintas batas di kedua negara. Perspektif keamanan kesehatan berbasis masyarakat digunakan untuk menganalisis perluasan ancaman kesehatan dan peran diplomasi perbatasan dalam mengatasi ancaman kesehatan masyarakat. Analisis ini mengungkapkan tiga isu penting: (1) mendefinisikan kembali paradigma keamanan perbatasan, (2) memposisikan diplomasi keamanan kesehatan perbatasan sebagai mekanisme kolaboratif, dan (3) partisipasi masyarakat perbatasan dalam diplomasi keamanan perbatasan. Penelitian ini memberikan kontribusi penting bagi pengembangan model kolaboratif diplomasi keamanan kesehatan perbatasan melalui partisipasi masyarakat dalam meningkatkan keamanan kesehatan di wilayah perbatasan kedua negara. Temuan ini menawarkan alternatif kebijakan keamanan kesehatan dalam diplomasi perbatasan antara Indonesia dan Timor Leste dan daerah perbatasan lainnya di Indonesia. Kata-kata Kunci: Keamanan kesehatan perbatasan, diplomasi kesehatan, pemberdayaan masyarakat, Indonesia-Timor Leste, Covid-19